Main Character’s Speech Functions Analysis In The Movie “Turning Red” - Luh Angelique Vironica Wardhana; Sang Ayu Isnu Maharani (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
The study entitled “An Analysis of The Main Character's Speech Functions in The Movie "Turning Red"”. It aims to identify the types of the speech functions and to find out the most prominent speech functions used by the main character named Meilin Lee. The research method used in this study is the qualitative method with the elaboration in the discussion. Furthermore, the analysis of this study used the theory proposed by Holmes (2013) which is the five of speech functions (expressive, directive, referential, metalinguistic, poetic, and phatic functions). The findings show that there are only three speech functions found in the movie Turning Red. They are the expressive function (17 cases), directive functions (34 cases), and phatic functions (26 cases). In addition, the most prominent speech functions used by the main character are the directive functions which serve thirty-four cases, followed by phatic that has twenty-six, and expressive that has only seventeen cases